Physical manipulation of biological and chemical syntheses for nanoparticle shape and size control - Ogale, Satishchandra B.; Ahmad, Absar; Pasricha, R.; Dhas, Vivek V.; Syed, A. (Applied Physics Letters, 2006)
A nanosynthesis scheme is demonstrated which renders excellent control of nanoparticle shape, size, and dispersity in a solution based synthesis process. The scheme, termed as percolative microcavity synthesis, involves the use of a granular medium with percolative microcavities which facilitate nearly similar grain size/shape dependent reaction zones limiting intrinsic growth inhomogeneities, enabling particle size/shape control. The viability of the process is demonstrated for the synthesis of gold nanoparticles by a plant extract based biological method as well as a chemical method. (c) 2006 American Institute of Physics.

Production, purification, and characterization of taxol and 10-DABIII from a new endophytic fungus gliocladium sp isolated from the Indian yew tree, taxus baccata - Sreekanth, D.; Syed, A.; Sarkar, S.; Sarkar, Dhiman; Santhakumari, B.; Ahmad, Absar; Khan, Mohammad Islam (Journal of Microbiology and Biotechnology, 2009)
We have isolated endophytic fungi from the Indian yew tree, Taxus baccata, and then screened for taxol production. Out of the 40 fungal cultures screened, one fungus Gliocladium sp. was found to produce taxol and 10-DABIII (10-deacetyl baccatin III). These compounds were purified by TLC and HPLC and characterized using UV-spectroscopy, ESI-MS, MS/MS, and proton NMR. One liter of Gliocladium sp. culture yielded 10 mu g of taxol and 65 mu g of 10-DABIII. The purified taxol from the fungus showed cytotoxicity towards cancer lines HL-60 (leukemia), A431 (epidermal carcinoma), and MCF-7 (breast cancer).
Keywords: 10 DAB III; Endophytic fungi; Gliocladium sp.; Taxol; Taxus baccata

Gold nanoconjugates reinforce the potency of conjugated cisplatin and doxorubicin - Iram, S. (Colloids and Surfaces B: Biointerfaces, 2017)
Osteosarcoma or osteogenic sarcoma is the most common and prevalent cancerous tumor of bone and occurs especially in children and teens. Recent treatment strategy includes a combination of both chemotherapy and surgeries. Although, the use of single drug-based chemotherapy treatment remains unsatisfactory. Therefore, combinatorial therapy has emerged as a potential strategy for treatment with limited side- effects. Here, we evaluated the combinatorial anticancerous effect of cisplatin (CIS) and doxorubicin (DOX) bioconjugated bromelain encapsulated gold nanoparticles (B-AuNPs conjugated CIS and DOX) in the treatment of osteosarcoma. The synthesized B-AuNPs conjugated CIS and DOX were characterized by various characterization techniques like UV–vis spectroscopy, TEM, DLS and zeta potential to ensure the synthesis, size, shape, size distribution and stability. Drug loading efficiency bioconjugation of CIS and DOX was ensured by UV–vis spectroscopy. Bioconjugation of CIS and DOX was further confirmed using UV–vis spectroscopy, TEM, DLS, Zeta potential and FT-IR analysis. The combinatorial effect of CIS and DOX in B-AuNPs conjugated CIS and DOX showed highly improved potency against MG-63 and Saos-2 cells at a very low concentration where primary osteoblasts didn't show any cytotoxic effect. The apoptotic effect of B-AuNPs conjugated CIS and DOX on osteosarcoma and primary osteoblasts cells were analyzed by increased permeability of the cell membrane, condensed chromatin and deep blue fluorescent condensed nucleus. The results clearly showed that B-AuNPs conjugated CIS and DOX significantly improved the potency of both the chemotherapeutic drugs by delivering them specifically into the nucleus of cancer cells through caveolae-dependent endocytosis. Thus, the greater inhibitory effect of combinatorial drugs (B-AuNPs conjugated CIS and DOX) over single drug based chemotherapy would be of great advantage during osteosarcoma treatment.
Keywords: cells; chemotherapy; Cytology; Cytotoxicity; Drug interactions; dynamic light scattering; Gold; Molecular Biology; Platinum Compounds